Assessing the impact of polyphenol-rich plant extracts on ice cream meltdown behavior and structural elements using multivariate analysis - Hesti Ayuningtyas Pangastuti; Songsak Wattanachaisaereekul; Praphan Pinsirodom (Applied Food Research)
Plant extracts are a rich source of polyphenols and become popular as a functional ingredient in ice cream products. However, addition of polyphenols in an ice cream mix can influent its structure and meltdown parameters. The objective of this study was to understand the effects of polyphenol-rich plant extracts on ice cream meltdown behavior and structural elements. Four plant extracts (grape seed, green tea, pomegranate, and roselle) were incorporated into ice cream mixes at 1, 2, and 3 wt % concentrations. All extracts resulted in ice creams with higher initial drip times (239–1421.5 s) and time to 50 % drip-through (1930–3397 s) with a concentration dependence compared to the control (234 and 1632 s, respectively), ranking highest to lowest as follows: green tea, grape seed, roselle, and pomegranate. The ice creams incorporating extracts could be classified into four distinct groups based on structural elements. The first group included green tea and pomegranate sample, which exhibited relatively high flow behavior index and low consistency coefficient. The second group was grape seed extract, characterized by high viscosity and low overrun. The third group comprised 2 % and 3 % roselle extract samples, with high fat globule size, and the fourth group solely the 1 % roselle extract, which showed high overrun. The results demonstrate that polyphenol-rich plant extracts can modify ice cream meltdown behavior due to changing its structural elements, and different polyphenol-rich plant extracts delay meltdown via specific mechanisms. These findings offer valuable insights for the application of plant extracts in ice cream quality modification.